Properties of Azotobacter as biofertilizer and biocontrol of Fusarium - Reginawanti Hindersah; Vera Oktavia Subardja; Pujawati Suryatmana; Rija Sudirja (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2024)
The Nitrogen-fixer bacteria, Azotobacters, are the potential Plant Growth Promotion Rhizobacteria for increasing plant growth and productivity due to their prominent role as biofertilizer dan bioprotectant. The objective of the experiment was to identify the plant-growth related characteristic of various Azotobacter isolates and to test their antagonism to soil-borne pathogen Fusarium. The five Azotobacter isolates were grown in Nitrogen-free slant for determining their ability to fix the Nitrogen, producing phytohormones and exopolysaccharides, and to inhibit the growth of Fusarium oxysforum f.sp. batatas. The results verified that all isolates synthesize various concentration of Indole acetic acid, Gibberellin, Zeatin and Kinetin as well exopolysaccharide in the N-free media. However, this study found that Azotobacter AzV1 did not detected to fix the N. This study suggests that Azotobacter has a dual function as biofertilizer and bioprotectant.